Upaya Meningkatkan Minat Baca dan Kesadaran Literasi Siswa Melalui Program KKN di Desa - Risky Pratama Hendrawan; Zanuar Hafidz Asani Hanand; Enjelika; Serlinawati; Amelia; Fanie Mardina Putri; Rahmad Afifullah; Gabriela Elsandika (LP2M Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The Literacy Culture Work Program was implemented by students of the Regular Community Service Program (KKN) Period I from the University of Palangka Raya in Kandris Village, Karusen Janang District, East Barito Regency. The program aimed to enhance reading interest and literacy skills among students at SDN and TK Mandiri Kandris. Activities included teaching, literacy education on social issues, school environmental greening, and decorating school walls with inspirational words. Despite challenges such as low reading interest and an unclean school environment, the program successfully motivated students to become more engaged in reading and learning. The outcomes indicated increased participation and literacy awareness among students. The program's sustainability is expected to strengthen the literacy culture in Kandris Village and improve the quality of human resources in the region.